The Hippo pathway as a drug target in gastric cancer. (28th April 2018) - Qiao, Yiting; Li, Tongyu; Zheng, Shusen; Wang, Hangxiang
Abstract: The Hippo tumor suppressor pathway is critical for balancing cellular differentiation and proliferation in response to cell-cell contact, mechanical signals and diffusible signals such as lysophosphatidic acid. Hippo pathway signaling is frequently dysregulated in gastric cancer (GC), as well as many other kinds of solid tumors, contributing to multiple aspects of malignant progression including unchecked cell division and metastasis. Considering the importance of this Hippo pathway in cancer, its pharmacological disruption may be of huge benefit in the fight against this disease. In this review, we summarize the components of the Hippo pathway, its crosstalk with other major oncogenic signaling pathways, common mechanisms of its dysregulation, as well as potential therapeutic approaches of targeting this pathway for cancer treatment, specifically in a GC context. Highlights: This review highlighted the clinical significance of Hippo pathway in gastric cancer from the aspects of functions and mechanisms of dysregulation. This review summarized the interplay between Hippo pathway and H. pylori infection, one of the strongest risk factors for gastric cancer. This review conducted a comprehensive discussion regarding advances for targeting Hippo pathway for the treatment of cancer, including gastric cancer.